2020
DOI: 10.1101/2020.09.06.284976
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Notable sequence homology of the ORF10 protein introspects the architecture of SARS-COV-2

Abstract: The global public health is endangered due to COVID-19 pandemic, which is caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). Despite having similar pathology to MERS and SARS-CoV, the infection fatality rate of SARS-CoV-2 is likely lower than 1%. SARS-CoV-2 has been reported to be uniquely characterized by the accessory protein ORF10, which contains eleven cytotoxic T lymphocyte (CTL) epitopes of nine amino acids length each, across various human leukocyte antigen (HLA) subtypes. In this s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…The absence of this stop codon in the pangolin (which exhibited synonymous mutations at the same locus) and SARS-CoV-2 viruses could result in a longer isoform of the ORF10 or fundamental changes in its function and expression levels. In a previous study of SARS-CoV-2 and pangolin-CoV genomes, position 26 was also identified as a region of population level variation from Tyr and His which significantly modifies the secondary structure of the coil region of the protein [52].…”
Section: Discussionmentioning
confidence: 98%
“…The absence of this stop codon in the pangolin (which exhibited synonymous mutations at the same locus) and SARS-CoV-2 viruses could result in a longer isoform of the ORF10 or fundamental changes in its function and expression levels. In a previous study of SARS-CoV-2 and pangolin-CoV genomes, position 26 was also identified as a region of population level variation from Tyr and His which significantly modifies the secondary structure of the coil region of the protein [52].…”
Section: Discussionmentioning
confidence: 98%
“…According to Hassan et al 2020, a MoRF was predicted to occur in residues 3-7. 12 A unique feature associated with MoRFs is their ability to exist in semi-disordered (i.e. flexible) states until binding, after which they can assume designated secondary structures.…”
Section: Discussionmentioning
confidence: 99%
“…The exact implications are unclear, but the ORF10 protein contains high numbers of promiscuous cytotoxic T lymphocyte (CTL) epitopes, primarily on the α-helix. 12,15 A recent study by Liu et al 2020 found that in severe cases of COVID-19, the ORF10 was overexpressed when compared against ORF10 expression levels in moderate cases. 16 If the ORF10 protein is synthesized, this may help to partially explain the nature behind severe cases of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of this stop codon in the pangolin (which exhibited synonymous mutations at the same locus) and human adapted viruses could result in a longer isoform of the ORF10 or fundamental changes in its function and expression levels. In a previous study of SARS-CoV-2 and pangolin-CoV genomes, position 26 was also identified as a region of population level variation from Tyr and His which significantly modifies the secondary structure of the coil region of the protein [55].…”
Section: Discussionmentioning
confidence: 99%